PENINGKATAN MUTU PENDIDIKAN DALAM PERSPEKTIF PSIKOLOGI SUFISTIK - Zuhri, Zuhri (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2014)
AbstractEffort to improve the quality of education a necessity for the people who want toget ahead, because the quality of education that will produce qualified humanresources to compete and exceed with other nations, which can produce workand creativity in all aspects of life, to realize these goals, become responsibility ofgovernment and the community as a provider of infrastructure while theeducator responsible for the learning process in this case is not only a variety offacility and allowance obtained but the more urgent is the spirit and motivationof religion as a driving force of progress or Sufi psychological factors.Keyword: mutu pendidikan, psikologi sufistik